Social Welfare in the Perspective of the Newspaper and Human Rights: Conceptual Study of Implementation in Orphanages - AM, Memi Pratiwi; Abubakar, Achmad; Sohrah, Sohrah (Perpustakaan dan Penerbitan Unismuh Makassar, 2025)
This conceptual study explores the integration of Qur’anic principles on human rights and social welfare with a focus on orphanages as institutions that uphold the rights and dignity of vulnerable children. By employing a qualitative approach through thematic (maudu’i) interpretation of selected Qur’anic verses, supported by hadith and scholarly literature, this study investigates the implementation of Islamic values—such as justice, compassion, and social responsibility—in the operational frameworks of orphanages in Indonesia. Findings reveal that although the Qur’an does not explicitly articulate modern legal terminology of human rights, its core teachings promote universal principles including the right to life, dignity, education, and protection for orphans and the needy. Orphanages are seen as practical embodiments of these principles, providing care, shelter, education, and emotional support. However, many face systemic challenges, including limited resources, poor management, and lack of integration with broader social programs. This study contributes to the discourse by highlighting the need for institutional reform that aligns with both Qur’anic mandates and international human rights standards. Practical recommendations include enhancing institutional capacity, improving transparency, encouraging government–civil society collaboration, and fostering community involvement. The research underscores the Qur’an’s relevance as a moral foundation for social justice and offers a holistic framework for improving the welfare of orphans through faith-based and rights-based approaches.